Calorie Intake of UKRIDA Students, Jakarta, Indonesia in 2021 - Dede Okky Tri Nurhasanah; Gracia J. M. T Winaktu; Luciana Budiati Sutanto; Hartanto Hartanto (World Nutrition Journal, 2022)
Calorie intake plays an important role in muscle contraction, concentration and organ functions. The recommendation of calorie intake, based on Indonesian RDA (AKG) 2019 for young adults, is 2250 kcal/day for women and 2650 kcal/day for men. Lack of calorie intake still occurs in faculty of medicine students in Semarang. This study aims to investigate the calorie intake of UKRIDA students, Jakarta, Indonesia in 2021.